Influence of fast neutron irradiation on the phase composition and optical properties of homogeneous SiOx and composite Si–SiOx thin films - Nesheva, Diana; Fogarassy, Zsolt; Fabian, Margit; Hristova-Vasileva, Temenuga; Sulyok, Attila; Bineva, Irina; Valcheva, Evgenia; Antonova, Krassimira; Petrik, Peter (Journal of materials science, 2021)
Layers and devices utilizing semiconductor nanocrystals have been the subjects of intensive research due to applications in opto- and microelectronic devices, solar cells, detectors, memories and in many more fields. We have shown previously that those nanocrystals in dielectric matrices undergo a substantial reformation during electron irradiation. The research of the interaction between semiconductor nanoclusters and irradiation is important for both the intentional modification of the structures and for understanding the stability of those devices under harsh, radiative conditions (e.g. space, nuclear, medical diagnosis, or similar applications). In the present research, we investigated the influence of neutron irradiation on substoichiometric silicon oxide. We investigated both homogeneous case and inhomogeneous case of matrices with silicon nanoclusters. We found that a fast neutron flux of 5.5 × 10 13 neutrons/cm 2 s and a fluence of 3.96 × 10 17 neutrons/cm 2 induce phase separation in the homogeneous films, whereas it decreases the volume fraction of the amorphous silicon phase caused by the reducing size of amorphous nanoclusters in the inhomogeneous films.